2020
DOI: 10.1186/s12903-020-1034-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-significant association between − 330 T/G polymorphism in interleukin-2 gene and chronic periodontitis: findings from a meta-analysis

Abstract: Background Chronic periodontitis (CP) is an immune-inflammatory disease that promotes tissue damage around the teeth. Among the several inflammatory mediators that orchestrate the periodontitis, there is the interleukin (IL)-2. Genetic variations in IL2 gene may be associated with the risk and severity of the disease. Contrary results are available in the literature with inconclusive findings and none meta-analysis to gather these data. Methods A literature search was performed for studies published before Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Sixth, we have evaluated one single polymorphism, other genetic variations may influence the rs1333 role in these inflammatory conditions. Previous studies available in the literature already showed the considerable impact of genetic polymorphisms and IBD [73], periodontitis [74][75][76][77][78][79] and SLE [80,81] further studies are required to validate our results.…”
Section: Discussionmentioning
confidence: 50%
“…Sixth, we have evaluated one single polymorphism, other genetic variations may influence the rs1333 role in these inflammatory conditions. Previous studies available in the literature already showed the considerable impact of genetic polymorphisms and IBD [73], periodontitis [74][75][76][77][78][79] and SLE [80,81] further studies are required to validate our results.…”
Section: Discussionmentioning
confidence: 50%
“…In a case-control study, the higher frequencies of the IL2 (+166, −330) haplotype were observed in patients with chronic periodontitis, when compared to controls of a mixed population [56]. In a recent meta-analysis, though, a non-significant association between 330 T/G polymorphism in the IL2 gene and chronic periodontitis, in any allelic evaluation, was reported [57].…”
Section: Cytokinesmentioning
confidence: 97%
“…TGF-β is a family of polypeptide growth factors involved in the inflammatory process and in regulation of the immune response [80]. Elevated TGF-β1 levels were found in patients with periodontitis, both in gingival tissue and in gingival fluid [57]. However, to date, no relationship has been found between the occurrence of chronic periodontitis and TGF-β1 encoding gene polymorphisms: −509 (C → T), −800 (G → A), −988 (C → A), +869 (T → C) and +915 (G → C) [80].…”
Section: Cytokinesmentioning
confidence: 99%
“…Recent literature surveys have revealed con icting outcomes regarding the relationship between in ammatory factors and periodontitis. For example, one study found a correlation between IL-2 gene promoter polymorphisms and periodontitis [14] , while others proposed that IL-2 promoter gene polymorphisms might not be linked to susceptibility to periodontitis [15] . As a result, a comprehensive elucidation of the in ammatory factors in uencing the risk of periodontitis and their respective contributions is still necessary.…”
Section: Introductionmentioning
confidence: 99%